Greening in the Caribbean? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
T Goguey, Head of the Fruit Trees Programme of CIRAD, France, is keen to correct our news item on citrus greening or Huanglongbing in Spore 82: 'Regarding your information about the arrival of greening in the Caribbean, I would like to point out...